The erosion of materials - Feng, Zheng; Feng, Zheng (Centre for Materials Engineering, 2017)
Solid particle erosion tests of glass, stainless steel, WC-Co and sintered alumina, have been performed with seven erodents using a range of particle diameters D (63 μm - 1000 μm), velocities V (33 m.s⁻¹ - 131 m.s⁻¹ ) and impact angles α (30° - 90°). The seven erodents are steel shot, glass beads, silica, alumina, tungsten carbide, silicon carbide and diamond· particles. In addition, the target materials have been subjected to cavitation erosion using a conventional ultrasonic horn in distilled water. Systematic studies of the influence of the impact variables on the erosion rate have been made. Scanning electron microscopy of the eroded surfaces and the erodents after impact has been performed. Empirical correlations between erosion rate and the parameters of erosion and the erodents were obtained and are discussed in terms of the modes and mechanisms of erosion. A semi-quantitative theoretical model has been developed to explain the empirical correlations for brittle and ductile materials. The mode of erosion of glass impacted by irregularly shaped particles is associated with the formation and interaction of lateral cracks over all impact velocities and angles used in this study. The erosion of glass by spherical particles is determined by particle size, impingement velocity and angle. An erosion map, in which the erosion of glass is mapped against velocity and particle size, has been constructed to categorise the types of damage observed in glass for impingement angles between 90° and 30°. The erosion. behaviour of 304 stainless steel is associated with cutting or ploughing and plastic accumulation processes. The erosion of WC-Co is associated with a combination of ductile and brittle modes of erosion. The erosion of alumina is brittle and associated with intergranular spallation and grain-crushing. An analysis of the results reveals that for the brittle materials, glass and alumina, the erosion rate is determined by kinetic energy, particle size and the relative hardness and toughness of the erodents. However, for ductile materials, the shape and kinetic energy of erodents are the most important factors determining the erosion rate. There is no significant effect of hardness and toughness of erodents on erosion. Surprisingly, the erosion resistance of the softer 304 stainless steel is better than that of alumina and WC-Co when hard erodents are used at impact angle greater than 40°. On the other hand the erosion resistance of the harder WC-Co and alumina is better than that of 304 stainless steel for softer erodents like silica erodents. Glass always exhibits poor erosion resistance. In cavitation erosion, stainless steel exhibits better cavitation erosion resistance than glass, alumina and WC-Co. The cavitation erosion resistance of WC-Co is dependent upon the cobalt content. An attempt to rationalise the results in terms of mechanisms has been made. Both solid particle and cavitation erosion rate for the as received glass is higher than that for the tempered glass due to introduction of residual compressive stresses into the surface by the tempering process. Particularly, it reveals that compressive stresses are more efficient in preventing the formation and propagation of Hertzian cracks. These findings will assist in the choice and design of materials that undergo both particle and cavitation erosion under specified conditions.